A Pseudo-longitudinal Study of Intranet Use in Hospitals - Fong, S.; Quaddus, Mohammed (Emerald Group Publishing, 2012)
Purpose – This paper investigates the roles of the time for system enhancement, work place relocation, and other organizational constructs, such as organization support, task characteristics, intranet characteristics and user characteristics in the use of intranet and web-enabled applications (IWAs) for supporting management accounting in public hospitals.Design/methodology/approach – The research was carried out in Hong Kong public hospitals, and a pseudo-longitudinal study spans a duration of one-and-a-half years to observe changes that occur over time. A two-phased survey research which investigated how the use of IWAs supports management accounting was also conducted for this study.Findings – The survey results unearthed a number of findings. In the phase I survey, intranet user information satisfaction had a direct significant impact on information quality of management accounting systems (MASIQ). The extent of task characteristics also improves the performance of MASIQ. However, mixed research results were found regarding the presence of top management support and IS experience of users and their contribution to intranet user information satisfaction and MASIQ. User training also did not show any significant impact on intranet user information satisfaction and MASIQ. The phase II survey results reflect two additional findings. First, workplace relocation (one office management practice) was found to have a negative impact on the support of management accounting. Second, the time for system enhancement improves the acceptance of IWAs in public hospitals.Research limitations/implications – The study provides support for certain prior research findings though some other findings were not consistent with expectations. The study was based on 157 hospital executives in the phase I survey and 147 hospital executives in the phase II survey. The findings are generalized reliably to the population studied – Hong Kong public hospitals. More research is needed for explorations of these findings. The research results contribute to the knowledge of uses of intranet for management accounting and control in public hospitals.Practical implications – The research offers insights into management accounting and control systems, as they are implemented through intranet in public hospitals. Work place relocation is less effective for grouping talents to work in offices at different locations. Face-to-face communication at a workplace is more efficient than communication through intranet applications. The study reinforced the belief that top management support is of prior concern in improving managerial performance.Originality/value – The roles of IWAs on the time for system enhancement and workplace relocation have not previously been studied. The results provide some useful support of prior findings and some modifications as well as extensions that further understanding in these areas.